PLANT-POLLINATOR INTERACTIONS FROM FLOWER TO LANDSCAPE The long and the short of it: a global analysis of hawkmoth pollination niches and interaction networks - Johnson, Steven D.; More, Marcela; Amorim, Felipe W. [UNESP]; Haber, William A.; Frankie, Gordon W.; Stanley, Dara A.; Cocucci, Andrea A.; Raguso, Robert A. (Wiley-Blackwell, 2017)
1. Proboscis length has been proposed as a key dimension of plant pollination niches, but this niche space has not previously been explored at regional and global scales for any pollination system. Hawkmoths are ideal organisms for exploring pollinator niches as they are important pollinators in most of the biodiverse regions of the earth and vary greatly in proboscis length, with some species having the longest proboscides of all insects. 2. Using data sets for nine biogeographical regions spanning the Old and New World, we ask whether it is possible to identify distinct hawkmoth pollination niches based on the frequency distribution of proboscis length, and whether these niches are reflected in the depths of flowers that are pollinated by hawkmoths. We also investigate the levels of specialization in hawkmoth pollination systems at the regional and community level using data from interaction network studies. 3. We found that most regional hawkmoth assemblages have bimodal or multimodal distributions of proboscis length and that these are matched by similar distributions of floral tube lengths. Hawkmoths, particularly those with longer proboscides, are polyphagous and at the network level show foraging specialization equivalent to or less than that of bees and hummingbirds. In the case of plants, shorter-tubed flowers are usually visited by numerous hawkmoth species, while those that are longer-tubed tend to exclude shorter-proboscid hawkmoths and thus become ecologically specialized on longer-proboscid hawkmoth species. Longer-tubed flowers tend to have greater nectar rewards, and this promotes short-term constancy by longproboscid hawkmoths. 4. Our results show that pollinator proboscis length is a key niche axis for plants and can account for the patterns of evolution in functional traits such as floral tube length and nectar volume. We also highlight a paradoxical trend for nectar resource niche breadth to increase according to proboscis length of pollinators, while pollinator niche breadth decreases according to the tube length of flowers.
Keywords: adaptive radiation; biogeography; co-evolution; community ecology; ecological shifts; floral adaptation; long-tongued; nectar; Sphingidae